Copper-instigated modulatory cell mortality mechanisms and progress in kidney diseases - Xiya Ren; Limei Zhao; Yajie Hao; Xiu Huang; Guangna Lv; Xiaoshuang Zhou (Renal Failure)
Copper is a vital cofactor in various enzymes, plays a pivotal role in maintaining cell homeostasis. When copper metabolism is disordered and mitochondrial dysfunction is impaired, programmed cell death such as apoptosis, paraptosis, pyroptosis, ferroptosis, cuproptosis, autophagy and necroptosis can be induced. In this review, we focus on the metabolic mechanisms of copper. In addition, we discuss the mechanism by which copper induces various programmed cell deaths. Finally, this review examines copper’s involvement in prevalent kidney diseases such as acute kidney injury and chronic kidney disease. The findings indicate that the use of copper chelators or plant extracts can mitigate kidney damage by reducing copper accumulation, offering novel insights into the pathogenesis and treatment strategies for kidney diseases.